2019
DOI: 10.1177/1553350619890736
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With a New Robotic Surgical System for Cholecystectomy

Abstract: Background. Laparoscopic cholecystectomy has been the gold standard treatment for symptomatic cholelithiasis for more than 3 decades. Robotic techniques are gaining traction in surgery, and recently, the Senhance™ robotic system was introduced. The system offers advantages over other robotic systems such as improved ergonomics, haptic feedback, eye tracking, and usability of standard laparoscopic trocars and reusable instruments. The Senhance was evaluated to understand the feasibility, benefits, and drawbacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
(20 reference statements)
0
24
0
2
Order By: Relevance
“…We attempted to control for this variable by only including studies after 2010; however, it is possible that some of the data remain influenced by this factor. Indeed, while 90% of the reviewed studies acknowledged the possibility of a learning curve, only five reported data and assessment on these trends [14,19,26,50,55]. The learning curve also applies to the OR staff's setup and takedown of the robot unit and to the flow of the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to control for this variable by only including studies after 2010; however, it is possible that some of the data remain influenced by this factor. Indeed, while 90% of the reviewed studies acknowledged the possibility of a learning curve, only five reported data and assessment on these trends [14,19,26,50,55]. The learning curve also applies to the OR staff's setup and takedown of the robot unit and to the flow of the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Three groups were formed to address this. The first included studies that compared techniques using the same number of ports (seven compared techniques with multi-ports [14,15,23,32,43,44,57]; 12 compared techniques with single ports [18, 20, 26-28, 34, 41, 45, 50, 53, 56, 58]), and of these, two were RCTs [27,32], and one was a propensity-matched analysis [43]. The second group included those comparing single-port robot-assisted with multi-port laparoscopic cholecystectomy (12 studies [13,19,22,29,30,38,40,42,46,54,55,59], including two RCTs [38,46] and one propensity-matched analysis [30]).…”
Section: Literature Searchmentioning
confidence: 99%
“…Since the initial reports of the use of the Senhance robotic platform in gynaecology 9 and colorectal surgery, 7 subsequent studies have confirmed the safety and feasibility of this system in abdominal procedures, [10][11][12][13] including colorectal surgeries. [14][15][16][17][18] In addition, previous publications have demonstrated its economic advantage over other systems for hysterectomy.…”
Section: Resultsmentioning
confidence: 96%
“…The recently introduced Senhance surgical robotic system can transmit haptic feedback to the surgeon, and provides an eye‐tracking camera control system, operator comfort, and reusable endoscopic instruments that enable starting the surgery with uncomplicated and highly standardized procedures. This system has already been used clinically in Europe and the United States, and there have been reports of its use in many surgical procedures, including colorectal cancer surgery 2–6 . However, it has only been introduced at four institutions in Japan, including our hospital.…”
Section: Introductionmentioning
confidence: 99%